2014
DOI: 10.1016/j.jcmg.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 Mapping in Transthyretin Amyloidosis

Abstract: Native myocardial T1 mapping detects cardiac ATTR amyloid with similar diagnostic performance and disease tracking to AL amyloid, but with lower maximal T1 elevation, and appears to be an early disease marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
245
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(257 citation statements)
references
References 21 publications
4
245
0
8
Order By: Relevance
“…In this context native T1 mapping offers great potential for accurate identification of amyloidosis [6]. Compared to other diseases, the native T1 values are much higher in amyloidosis and the ECV values are also clearly elevated as further studies showed [6,63]. Therefore, T1 mapping might be applicable as an early disease marker due to the detection of global myocardial changes.…”
Section: Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…In this context native T1 mapping offers great potential for accurate identification of amyloidosis [6]. Compared to other diseases, the native T1 values are much higher in amyloidosis and the ECV values are also clearly elevated as further studies showed [6,63]. Therefore, T1 mapping might be applicable as an early disease marker due to the detection of global myocardial changes.…”
Section: Amyloidosismentioning
confidence: 99%
“…Therefore, T1 mapping might be applicable as an early disease marker due to the detection of global myocardial changes. A recent study by Fontana et al showed that native T1 mapping even offers potential for the differentiation of AL amyloidosis and transthyretin amyloidosis [63]. Due to the absence of edema in amyloidosis, no T2 alterations are detected.…”
Section: Amyloidosismentioning
confidence: 99%
“…On T1 mapping, if the myocardium crosses the null point at a T1 time point prior to the blood pool, it indicates the presence of diffuse global hyperenhancement and is characteristic of cardiac amyloidosis. Native (pre-contrast) T1 times in patients with cardiac amyloidosis were significantly prolonged compared to hypertrophic cardiomyopathy and healthy subjects 60 . Native T1 mapping techniques may be particularly helpful in patients with renal dysfunction (due to risk of gadolinium toxicity).…”
Section: Magnetic Resonancementioning
confidence: 91%
“…Although native T1 and ECV data are helpful for early detection of cardiac involvement in systemic amyloidosis or suspected cardiac amyloidosis [45][46][47], the prognostic value of T1 mapping is rarely reported. T1 mapping can also provide information about disease severity and serve as a monitoring tool for chemotherapy in amyloid light-chain amyloidosis [48].…”
Section: Cardiac Amyloidosis and Sarcoidosismentioning
confidence: 99%